Laying Stress on Ideas: Actors, Connections, and Meanings of Sustainable Finance in Italy - Nupieri, Tiziana (SocietàMutamentoPolitica, 2024)
Although the idea of private investment as “essential for sustainability” has only recently been naturalized in European regulations (Hay 2004), the use of market instruments to address social-environmental challenges has long been established in Western societies. Since the “neoliberal revolution” of the late 1970s (Harvey 2005: 39), new modes of accumulation and regulatory processes have fostered the expansion of financial assets, a process known as financialization (Epstein 2005, Krippner 2005). Over the past 15 years, financial logic has permeated areas such as welfare, nature, and the environment. However, the literature still lacks a holistic analysis of the pervasive role of finance across all dimensions of sustainability, particularly in terms of “financialization of sustainability”. Social and economic actors play a pivotal role in constructing narratives that frame sustainability through market logic. Drawing on the référentiel approach (Jobert and Muller 1987), this paper explores sustainable finance discourses in Italy using a mixed-methods approach. It investigates the key actors disseminating information on the topic, the resources that position them as mediators, and the worldviews they embed in both discourse and policy.